2011
DOI: 10.1097/ccm.0b013e31821209be
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effects of argon in an in vivo model of transient middle cerebral artery occlusion in rats*

Abstract: We were able to demonstrate argon's neuroprotective effects in an in vivo experimental rat model of acute focal cerebral ischemia. Animals breathing spontaneously 50 vol % argon 1 hr after induction of transient middle cerebral artery occlusion for 1 hr by face mask showed significantly reduced infarct volumes and composite adverse outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
116
2
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(128 citation statements)
references
References 28 publications
7
116
2
3
Order By: Relevance
“…It was reported that argon was protective against hypoxia-induced injury in cultured neurons 21,22 . In an in vivo model of acute focal cerebral ischaemia in adult rats, exposure to 50% argon significantly reduced infarct volumes and neurological deficits after the occlusion 23 . Although noble gases are chemically inert, they are capable of forming induced dipole, which is attracted to the charge that induced it, or instantaneous dipole, which produces and binds to an induced dipole in a second molecule 24 .…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that argon was protective against hypoxia-induced injury in cultured neurons 21,22 . In an in vivo model of acute focal cerebral ischaemia in adult rats, exposure to 50% argon significantly reduced infarct volumes and neurological deficits after the occlusion 23 . Although noble gases are chemically inert, they are capable of forming induced dipole, which is attracted to the charge that induced it, or instantaneous dipole, which produces and binds to an induced dipole in a second molecule 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Similar to xenon, argon and helium have shown neuroprotective qualities in vitro (11)(12)(13)(14) and in vivo (13,19) while other members of noble gas family, neon and krypton, lack effect (11). Interestingly helium has also been reported to exhibit both detrimental as well as protective effects (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…Here, the neuroprotective properties of argon are well documented [5,7,9,25]. For example, Ryang et al [16] demonstrated significantly reduced infarct volumes after transient middle cerebral artery occlusion - without, however, influencing acute survival 24 h after the intervention. These positive, encouraging results inspired an investigation into the influence of argon on other organs.…”
Section: Discussionmentioning
confidence: 99%
“…All surgical procedures were performed under inhalation anesthesia as previously described [16]. To evaluate an effect of the inhalant argon, animals were exposed to either 50 vol% argon (argon group) or 50 vol% nitrogen (control group) balanced with 50 vol% oxygen for 60 min prior to injury (preconditioning).…”
Section: Methodsmentioning
confidence: 99%